Population pharmacokinetic analysis of transdermal granisetron in healthy Chinese and Caucasian volunteers - Li, Jiayu; Hu, Pei; Zhou, Li; Nagahama, Fumiko; Chen, Rui (Frontiers in Pharmacology, 2023)
Granisetron patch is a prolonged delivery transdermal system that used to prevent Chemotherapyinduced nausea and vomiting (CINV). To date, no pharmacokinetics comparison between Chinese and Caucasian population has been conducted for granisetron patch. This study focused on the ethnic differences in pharmacokinetics (PK) of granisetron transdermal delivery system (GTDS) between Chinese and Caucasians and the influence of demographic covariates on PK (age, weight, height, BMI, sex). To achieve this, blood concentration data from 112 Caucasian healthy subjects participating in four clinical trials and 24 Chinese healthy subjects from on clinical trial was collected after a single application of the GTDS. A nonlinear mixed-effects model method of Phoenix NLME software was used to establish a population pharmacokinetic (Pop PK) model for Caucasian subjects. Bootstrap and visual predictive check (VPC) were used to validate the model. Based on the analysis a one-compartment model with first-order absorption and a first-order elimination well described the PK characteristics of GTDS. The apparent systemic clearance was determined to be 31316.3 mL/h and the central compartment volume of distribution was 6299.03 L. None of the five covariates (age, weight, height, body mass index, and sex) included in the Pop PK were significant covariates affecting PK. The final Pop PK model was used to simulate the Caucasian blood concentration by applying dosing regimen used for Chinese population. Comparison of the simulated Caucasian PK data with observed clinical PK data from Chinese healthy subjects revealed no significant differences in the main parameters, AUClast and Cavg, between the two groups. These findings suggested that no dose adjustment was required when applied to the Chinese population. In conclusion, this Pop PK study comparing the transdermal patch in Chinese and Caucasian healthy subjects provided valuable insights for optimizing dosage across ethnicities.